Importance of personal branding as an employability strategy for university students (UNEVE). - Vázquez Ibarra, Irene; Valiente García, Itzel; López Espinosa, Irma (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2026)
OBJECTIVE: To identify the importance of personal branding as an employability strategy for students nearing graduation from two academic programs at the Universidad Estatal del Valle de Ecatepec. ​MATERIAL AND METHOD: This research followed a quantitative approach using non-probabilistic sampling. A questionnaire was administered to 160 students in their seventh and eighth semesters from the Business Humanities and Multimedia Communication programs. ​RESULTS: Although the majority of students recognize the value of personal branding and digital identity, few possess a strategic plan for their professional projection. ​CONCLUSIONS: Strengthening personal branding should be a priority in university education. It is recommended to integrate personal branding content into curricula and promote tutoring, workshops, and advisory sessions to prepare students for effective entry into the labor market.